Genetic analysis of long-lived families reveals novel variants influencing high density-lipoprotein cholesterol - Feitosa, Mary F.; Wojczynski, Mary K.; Straka, Robert; Kammerer, Candace M.; Lee, Joseph H.; Kraja, Aldi T.; Christensen, Kaare; Newman, Anne B.; Province, Michael A.; Borecki, Ingrid B. (Frontiers in Genetics, 2014)
The plasma levels of high-density lipoprotein cholesterol (HDL) have an inverse relationship to the risks of atherosclerosis and cardiovascular disease, and have also been associated with longevity. We sought to identify novel loci for HDL that could potentially provide new insights into biological regulation of HDL metabolism in healthy-longevous subjects. We performed a genome-wide association scan on HDL using a mixed model approach to account for family structure using kinship coefficients. A total of 4,114 subjects of European descent (480 families) were genotyped at ~2.3 million SNPs and ~38 million SNPs were imputed using the 1000 Genome Cosmopolitan reference panel in MACH. We identified novel variants near-NLRP1 (17p13) associated with an increase of HDL levels at genome-wide significant level (p< 5.0E-08). Additionally, several CETP (16q21) and ZNF259-APOA5-A4-C3-A1 (11q23.3) variants associated with HDL were found, replicating those previously reported in the literature. A possible regulatory variant upstream of NLRP1 that is associated with HDL in these elderly LLFS subjects may also contribute to their longevity and health. Our NLRP1 intergenic SNPs show a potential regulatory function in ENCODE; however, it is not clear whether they regulate NLRP1 or other more remote gene. NLRP1 plays an important role in the induction of apoptosis, and its inflammasome is critical for mediating innate immune responses. Nlrp1a (a mouse ortholog of human NLRP1) interacts with SREBP-1a (17p11) which has a fundamental role in lipid concentration and composition, and is involved in innate immune response in macrophages. The NLRP1 region is conserved in mammals, but also has evolved adaptively showing signals of positive selection in European populations that might confer an advantage. NLRP1 intergenic SNPs have also been associated with immunity/inflammasome disorders which highlights the biological importance of this chromosomal region.